1973
DOI: 10.1109/tau.1973.1162525
|View full text |Cite
|
Sign up to set email alerts
|

A computer program for designing optimum FIR linear phase digital filters

Abstract: This paper presents a general-purpose computer program which is capable of designing a large class of optimum (in the minimax sense) FIR linear phase digital filters. The program has options for designing such standard filters as lowpass, high-pass, bandpass, and bandstop filters, as well as multipassband-stopband filters, differentiators, and Hilbert transformers. The program can also be used to design filters which approximate arbitrary frequency specifications which are provided by the user. The program is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
276
0
4

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,028 publications
(280 citation statements)
references
References 8 publications
0
276
0
4
Order By: Relevance
“…Emphasis has been put on the optimization of the free parameter 1(1 > 0) of the delta operator in order to achieve minimum roundoff noise gain at the output. The second-order DFIIt section, being a basic building block, was analyzed in detail [3], [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emphasis has been put on the optimization of the free parameter 1(1 > 0) of the delta operator in order to achieve minimum roundoff noise gain at the output. The second-order DFIIt section, being a basic building block, was analyzed in detail [3], [4].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this result, the window method can be directly applied to design FIR FHT. After some maniputation, it can be shown that h (n) = cos( )h 0 (n) + sin( )h 1 (n) (3) where h1(n) is the impulse response of the conventional HT and h0(n) is equal to unit sample function (n). Thus, FHT can be designed by slightly modifying the filter coefficients of conventional HT, which can be obtained by several well-documented methods.…”
Section: A Definition and Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…(2) based on the Remez algorithm. 33 The corresponding amplitude and phase response of the first-, second-, and third-order differentiators as a function of the number of taps are also plotted in Figs. 1(a)-1(c).…”
Section: Operation Principlementioning
confidence: 99%
“…If a time domain (FIR) implementation of SSP is desired for real-time or near realtime processing, an efficient way ofrealizing the SSP bandpass filters exists based on a two-branch cascaded structure of filters of lower complexity capable of reducing the multiply count by up to 70% compared to the direct design approach [5]. The design is based on two lowpass filters with sparse non-zero coefficients and the application of the frequency scaling theorem as weil as the frequency modulation theorem.…”
Section: Implementa Tion With T Apped-dela Y Linesmentioning
confidence: 99%